PKM Penerapan Website Dan Pemasaran Digital Untuk UMKM Kotel Berbasis Kearifan Lokal Di Desa Gudang Besuki - Ahmad Hudawi AS; Della Prisilia Irani; Herlynda Firdaus Sholeha (CV. Akira Java Bulu, 2025)
The lack of digital identity, reliance on traditional marketing strategies, and limited digital literacy are the main challenges faced by micro, small, and medium enterprises (MSMEs) producing Kotel, a traditional seafood-based snack in Gudang Besuki Village. This community service program aims to enhance partners' competitiveness by implementing websites and digital marketing based on local wisdom. The method was designed participatively through problem identification, production training, management strengthening, and digital marketing assistance, including website development, social media activation, and e-commerce utilisation. Evaluation was done using pre-tests and post-tests with paired sample t-tests to measure knowledge and skill improvement. The program results show that partners successfully built a WordPress-based business website, produced product catalogues with local culture-based narratives, and utilised Instagram, WhatsApp, Google My Business, and Shopee as promotional media. Within two weeks, the Instagram account gained 150 followers and recorded six online transactions, while the average competency score of partners increased significantly from 65.63 to 81.38 (p < 0.001). These findings confirm that simple yet contextual digitalisation can expand market access and strengthen the competitiveness of local MSMEs. In conclusion, the application of websites and digital marketing strategies has proven effective in enhancing the independence and sustainability of Kotel businesses based on local wisdom. As a follow-up, training in digital financial management, QRIS payment system integration, e-commerce feature development on websites, and the formation of local digital entrepreneurship forums are recommended to strengthen networks and encourage replication in other regions.